Estimating the effects of United States food safety and agricultural health standards on agro-food exports from Latin America and the Caribbean - Artecona, Raquel (ECLAC Washington, D.C.US, 2010)
Studies the effects of technical standards on trade flows of selected agro-food sectors. Focuses on Latin American exports to the US market.